Analisis Sistem Pendaftaran Merek dalam Kasus Pembatalan Merek Zhe Nung Zhu (Studi Putusan Mahkamah Agung Nomor 704K/Pdt.Sus-HKI/2021) - Yolanda Pusvita Sari; Saidin; Hasim Purba (Jurnal Hukum Lex Generalis, 2025)
Indonesia applies the First to File trademark registration system based on Law No. 20 of 2016 on Trademarks and Geographical Indications which provides legal protection to the party who first registers their trademark, however its implementation faces challenges such as in the case of cancellation of the trademark "Zhe Nung Zhu & Lukisan" decided through Supreme Court Decision No. 704K/Pdt.Sus-HKI/2021. Through normative legal research with descriptive analytical approach using secondary data and qualitative analysis, it was found that the factors causing trademark cancellation include contradiction with state ideology and legislation, lack of distinctiveness, registration with bad faith, and similarity in essence with previously registered trademarks. Indonesia's trademark legal protection system implements layered mechanisms through preventive protection (administrative and substantive examination) and repressive protection (sanctions and cancellation mechanisms), where in the decision the Supreme Court applied Article 21 paragraph (1) letter a of Law No. 20 of 2016 by considering that the trademark "Zhe Nung Zhu & Lukisan" owned by Darma Iliadi has similarity in essence with the trademark "Lukisan" owned by Dhalim Soekodanu which has been registered since 1991 and was registered with bad faith, so cancellation is necessary to protect the rights of legitimate trademark owners and prevent consumer confusion.